Cross-sectional survey on public attitudes and factors related to physician-assisted dying in Taiwan - Kevin Chien-Chang Wu; Chun-Tung Kuo; Duan-Rung Chen (BMJ Open)
Objective To examine the public’s stance on physician-assisted dying (PAD) in Taiwan across different PAD scenarios and identify demographic and psychosocial factors associated with the levels of support.Design Cross-sectional survey design. Independent variables included individual sociodemographic characteristics, healthcare professionals, perceived quality of life, formal caregiver experience, Patient Right to Autonomy Act (PRAA) awareness and advance care planning (ACP) preparedness.Setting An online survey of the general population in Taiwan was conducted in 2022.Participants A total of 3922 Taiwanese adults who completed all survey questions.Outcome measures Agreement levels with PAD in three scenarios: terminal illnesses, unbearable non-terminal pain and severe cognitive impairments. Multivariate logistic regression was used to examine agreement with each PAD scenario as separate dependent variables in the first three models and overall agreement across all scenarios as the dependent variable in the fourth model.Results High levels of public support for PAD were observed, with 86.2% supporting PAD for terminal illnesses, 79.2% for unbearable non-terminal pain and 72.6% for severe cognitive impairments. Support for PAD was associated with factors including younger age, male gender, lack of religious affiliation, a non-healthcare professional background, employment as a formal caregiver, lack of awareness of PRAA and higher preparedness in ACP.Conclusions The results indicate a potential cultural shift in Taiwan towards greater emphasis on individual autonomy in end-of-life decisions. There appears to be significant public support for developing legal frameworks in favour of PAD, carefully considering the psychosocial factors that highlight the importance of individual rights in end-of-life care.